The Effects of Transportation Modes on Noise Pollution in Koya City - Hoshmand Jawhar Abbas; Serwan Arab Sadiq; Hamed Abdulla Salih; Sangar Ahmed Hussein (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
Transportation means including all kinds are considered the major and most dangerous source of noise since, on the one hand, they have highest contribution rate in causing noises, and on the other hand, they affect a great number of city inhabitants. Transportation means also has an immediate influence on the peacefulness and living balance amongst people because unnatural sounds creates noise and this causes psychological unrest and ruins the surrounding peace. The study problem is the existence of sound pollution in the selected area of the research which are caused by a number of seen and unseen sources. These sources have to be unveiled pointed to. Solving these problems scientifically and practically is of great benefit for the area. The main aim of this study is to identify the sound pollution sources in the city of Koya and its effects. The study also aims at proposing the best solution possible. Raising the awareness of people to protect the environment, following standard procedures, reducing pollution due to noises, and identifying noise sources. Research plan The aim of the study requires dividing the study into three sections. Section one refers to the theoretical outline of the area under study which includes three themes. The first theme discusses the technical terms and concepts, second theme deals with the major sound pollution sources, and the third one is dedicated to introducing the area of the study. While in section two we have analyzed the time distribution of the noises and their sources in Koya city. This section also have three themes, the first one id devoted to the place of the noise, the second one presents noise time distribution, and the last one light is shed on consequences and solutions of the noises.